(untitled) (Journal of the College of Basic Education, 2025)
The research talks about the intellectuals (writers, professors, university students, lawyers and other social groups) who enjoyed modern intellectual and political awareness. The purpose of the research is to see the political role of this group during an important period in Iranian history, which is the beginning of the rule of Mohammad Reza Pahlavi. The research methodology adopted is the descriptive approach in narrating historical events by collecting scientific material and describing it in an objective scientific manner. The researcher reached several results, including (The intellectuals in the country went through four stages, each stage represented a generation of intellectuals, and the intellectuals appeared and grew in Iranian society at the beginning of the nineteenth century. The intellectuals invested in the limited space of freedom that Shah Mohammad Reza Pahlavi allowed under pressure from foreign powers)